Tutor profile: Julianna O.
Find the derivative of f(x) = 6x^3 - 9x + 4
1. First, the power rule can give you the derivative for 6x^3: The power rule states that x^n, when derived, becomes nx^n-1 So then 6x^3 becomes 18x^2 2. Then, to derive 9x this is the multiplication by a constant rule: The multiplication by a constant rule states that cf, when derived, becomes cf' So then 9x becomes 9 3. Lastly, constants, when derived, become 0, so +4 becomes 0. 4. Lets put it all together! f'(x) = 18x^2 -9 is the final answer
Which of the following sentences contains a prepositional phrase? A. I don't know where she went. B. There was a dark stain on my shirt. C. Only the best foods make the menu. D. Whenever we get tired, we also get grumpy.
B. There was a dark stain on my shirt.
Equation: x+5 = 10-2x solve for x
1. Subtract 5 from both sides x+5-5 = 10-2x-5 x = 5-2x 2. Add 2x to both sides x+2x = 5-2x+2x 3x = 5 3. divide both sides by 3 3x/3 = 5/3 Final Answer: x = 5/3
needs and Julianna will reply soon.